When is it less costly for risky firms to borrow? Evidence from the bank risk-taking channel of monetary policy - Teodora Paligorova; Jo\~ao A. C. Santos (Bank of Canada, 2012)
In an investigation of banks' loan pricing policies in the United States over the past two decades, this study finds supporting evidence for the bank risk-taking channel of monetary policy. We show that banks charge lower spreads when they lend to riskier borrowers relative to the spreads they charge on loans to safer borrowers in periods of low short-term rates compared to periods of high short-term rates. The interest discount that banks offer riskier borrowers when short-term rates are low is robust to borrower-,loan-, and bank-specific factors as well as to macroeconomic factors known to affect loan rates. The discount is also robust to bank-firm fixed effects. Finally, our tests that build on the micro information banks provide on their lending standards in the Senior Loan Officers Opinion Survey suggest the interest rate discount that riskier borrowers receive when short-term rates are low is bank driven.
Keywords: G21; 330; Financial Institutions; Monetary policy framework